AB1100 Epidemiology and management practices for childhood-onset systemic lupus erythematosus patients: a survey in latin america. (12th June 2018) - Ferreira, J.C.; Trindade, V.C.; Espada, G.; Morel, Z.; Bonfa, E.; Saad-Magalhães, C.; Silva, C.A.
Abstract : Background: Two groups have reported data focused on epidemiology, clinical and laboratorial features of childhood-onset systemic lupus erythematosus (cSLE) patients in Latin America (LA): BRAC-SLE (Brazilian Childhood-onset SLE Registry Group) and GLADEL (Grupo Latino Americano De Estudio del Lupus). However, to the best of our knowledge, epidemiology and management of cSLE based on LA Paediatric Rheumatologists (LAPR) were not carried out. Objectives: Therefore, the objective of the present cross-sectional survey study was to assess LAPR reports of cSLE patients regarding epidemiology, classification criteria, disease activity and other instruments used in clinical practices, laboratory and other exams availability, general supportive care, drugs availability, infections, non-live vaccines, issues observed in adolescents, reproductive health issues and transition-focused program to adult care. Methods: A cross-sectional study was performed in 288 LAPR based on online survey about cSLE practices, which included 21 countries. All physicians are members of Pan-American League of Association for Rheumatology (PANLAR). Results: The response rate of web-based survey by LAPR was 170/288 (59%) and the majority worked in University Hospitals (63%). The ACR and/or SLICC classification criteria (99%) and disease activity tools (97%) were almost universally used by LAPR, whereas damage index (70%) and CHAQ (58%) instruments were less frequently used. Laboratory exams, diagnostic imaging and biopsies were generally available (>75%), however low availability for densitometry (66%). Drug access was excellent for the most common prescribed medications (>75%), except for belimumab (11%). Endemic illnesses were reported by LAPR in at least one cSLE patient during the previous year: tuberculosis (16%) and Hansen disease (2%). Emerging mosquito-borne diseases were also reported: dengue (20%), Chikungunya (11%) and Zika (8%). Groups were further divided in two, according to the number of cSLE patients followed by LAPR in the last year: group A ( 3 25 patients) and group B (< 25 patients). Frequencies of condom in combination with other contraceptive methods were significantly higher in group A than B (69% vs. 48%, p=0.01). The frequencies of reported pregnancy (50% vs. 16%, p<0.001) and non-adherence to therapy were significantly higher in group A (100% vs. 93%, p=0.023). Alcohol intake (42% vs. 21%, p=0.004) and illicit drug use (19% vs. 5%, p=0.007) were also reported more frequently by LAPR of group A in at least one cSLE patient. Conclusions: This first large web-based survey demonstrated an overall excellent access for diagnosis and therapy by LAPR, probably related to their high rate of practices in tertiary care of University Hospitals. Adherence to therapy, pregnancy and substance abuse were identified as major challenges in this population, particularly in larger centres. Acknowledgements: This study was supported by grants from Fundação de Amparo à Pesquisa do Estado de São Paulo FAPESP 2015/ 03756–4 to EB and CAS), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq 305068/2014–8 to EB, 301479/2015–1 to CSM and 303422/2015–7 to CAS). Disclosure of Interest: J. Ferreira: None declared, V. Trindade: None declared, G. Espada: None declared, Z. Morel: None declared, E. Bonfa: None declared, C. Saad-Magalhães: None declared, C. Silva Grant/research support from: Fundação de Amparo à Pesquisa do Estado de São Paulo FAPESP 2015/ 03756–4)